Nano indentation and morphology study of the polypropylene and high density polyethylene nanocomposites based on exfoliated graphite Nano platelets/Nano- magnesium oxide - I. Alateyah, A (International Journal of Engineering and Technology, 2018)
Polypropylene (PP) and high density polyethylene (HDPE) were successfully fabricated using injection molding machine, by the addition of exfoliated graphite nanoplatelets composites reinforced with 2wt.t% of nano-magnesia. The nanoindentation properties and microstructure of the composites were investigated, in the current study. The XRD patterns of both composites showed the peaks of xGnP and n-MgO, where their intensity became stronger with increasing the concentration of xGnP added into both polymers. In addition, the SEM micrographs revealed a good dispersion of fillers within the matrix. The nanoindentation properties of both nanocomposites revealed better properties with compared to the virgin polymers. The PP nanocomposites showed an improvement of hardness up to 22 % and 118% with the compositions of 1xGnP/2n-MgO and 5xGnP/2n-MgO respectively. In addition, HDPE/1xGnP/2n-MgO and HDPE/5xGnP/2n-MgO represented a dramatic improvement of hardness up to 146% and 341% respectively with compared to virgin polymer. In addition, the enhancements in reduced modulus of PP and HDPE were proportional to the xGNP loading.Â Â